2018
DOI: 10.1093/eurheartj/ehy486
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure and risk of aortic valve disease: a cohort analysis of 5.4 million UK adults

Abstract: AimsTo test two related hypotheses that elevated blood pressure (BP) is a risk factor for aortic valve stenosis (AS) or regurgitation (AR).Methods and resultsIn this cohort study of 5.4 million UK patients with no known cardiovascular disease or aortic valve disease at baseline, we investigated the relationship between BP and risk of incident AS and AR using multivariable-adjusted Cox regression models. Over a median follow-up of 9.2 years, 20 680 patients (0.38%) were diagnosed with AS and 6440 (0.12%) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 38 publications
(39 reference statements)
2
45
1
2
Order By: Relevance
“…In 2 large-scale studies that used data from electronic health records with BP as a continuous variable as in our study, over a median of 9 years' follow-up, exposure to 20-mm Hg higher BP was associated with a 41% greater risk of aortic stenosis, 38% greater risk of aortic regurgitation, and 26% greater risk of mitral regurgitation. 10,12 Our estimates are stronger than those reported in those large cohort studies. This difference might be related to residual confounding in earlier studies, which can bias associations toward the null.…”
Section: Discussioncontrasting
confidence: 87%
“…In 2 large-scale studies that used data from electronic health records with BP as a continuous variable as in our study, over a median of 9 years' follow-up, exposure to 20-mm Hg higher BP was associated with a 41% greater risk of aortic stenosis, 38% greater risk of aortic regurgitation, and 26% greater risk of mitral regurgitation. 10,12 Our estimates are stronger than those reported in those large cohort studies. This difference might be related to residual confounding in earlier studies, which can bias associations toward the null.…”
Section: Discussioncontrasting
confidence: 87%
“…A literature review revealed a higher incidence of systemic hypertension in patients with MS [ 25 ] but provided no explanation for it; the etiology could be the subject of a future prospective study aimed at investigating a possible causal relationship. Indeed, blood pressure elevation recently has been investigated as a risk factor for development of AS or AR [ 26 ]. We also found a significant relationship between TR and DM, which has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic valve sclerosis, or calcific aortic valve disease (CAVD), is an early stage of AVS and is marked by thickening and calcification of the valve tissue. Common risk factors to develop aortic valve sclerosis are high blood pressure, high blood lipid and cholesterol levels, obesity, diabetes mellitus, smoking, and chronic kidney disease [6,7,8,9,10,11]. The healthy human aortic valve is composed of three thin leaflets (<1 mm), each made up of three layers—the fibrosa on the aortic side, the spongiosa, and the ventricularis on the ventricular side of the valve (Figure 1; upper left).…”
Section: Introductionmentioning
confidence: 99%